Klotho: un nuevo eslabón en la fisiopatología de la insuficiencia renal crónica - Salech M., Felipe; Couve C., Andrés; Michea A., Luis; Alvo A., Miriam (Revista Hospital Clínico Universidad de Chile, 2010)
Klotho, a recently described gene, is mainly expressed in the kidney, and encodes a protein necessary for the activity of fibroblast growth factor receptors (FGFR), especially FGFR1. The Klotho protein has two variants, a transmembrane and a secreted form, and the latter may represent a new hormone synthesized by the kidney. Recent studies have shown that chronic kidney disease (CDK) is associated with significant alterations in the expression of klotho, and this alteration seems to be responsible for many of the phenotypic characteristics that accompany the uremic syndrome. CKD is associated with marked lymphocyte dysfunction, a clinically relevant problem, but the pathophysiological mechanisms behind this dysfunction are mostly unknown. Our research group has recently demonstrated the expression of klotho and FGFR1 in human lymphocytes and is currently implementing a series of experiments designed to determine the role of this pathway in the pathogenesis of lymphocyte dysfunction associated with uremia.